Pengaruh Kinerja Keuangan Terhadap Nilai Perusahaan pada Perusahaan Subsektor Kosmetik yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2022 - Shinta Friska Febriani Pranoto; Mawar Ratih Kusumawardani; Taufik Akbar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2022)
This study aims to analyze the Effect of Financial Performance on Firm Value in Cosmetics Subsector Companies Listed on the Indonesia Stock Exchange in 2016-2020, partially or simultaneously the data used in this study from the financial statements of 6 companies from 7 cosmetics subsector companies published through website www.id.co.id for the period 2016 to 2020. The sampling technique in this study used a purposive sampling technique. The data was then analyzed using panel data regression through the Eviews 10 program.Based on the results of the classical assumption test, partial test and simultaneous test, it can be concluded that the results of the classical assumption test indicate that it is not eligible and there is no problem that the data is normally distributed and significant from the normality test, multicollinearity test and heteroscedasticity test. The partial test shows that the current ratio (CR) has no significant effect on price to book value (PBV), return on assets (ROA) has no significant effect on price to book value (PBV), debt to equity ratio (DER) has no significant effect. on price to book value (PBV), and total asset turnover (TATO) has a significant effect on price to book value (PBV),